Formation of nano-structured core–shell micro-granules by evaporation induced assembly. Issue 103 (7th October 2015) - Das, Avik; Sen, D.; Mazumder, S.; Ghosh, A. K.; Basak, C. B.; Dasgupta, K.
Abstract : Nano-structured spherical micro-granules of core–shell morphology have been realized by utilizing the contrasting interfacial interaction of two different types of nano-particles with liquid solvent. Abstract : Nano-structured spherical micro-granules of core–shell morphology have been realized by utilizing the contrasting interfacial interaction of two different types of nano-particles with liquid solvent. By enforcing evaporation induced assembly, a hydrophobic core has been wrapped inside a hydrophilic envelope consisting of correlated nano-particles. This is realized by a one step, fast and facile technique of spray-drying. The evaporation of water in a radially outward direction from mixed-suspension droplets enforces the hydrophobic component to travel towards the core and the hydrophilic component to reside at the surface forming a shell. Mapping the coherent neutron and X-ray scattering length density into reciprocal space, the structure as well as inter-particle correlation in such micro-granules has been characterized over a wide range of wave-vector transfers. Scattering results have been complemented with electron microscopy. Significant enhancement in specific surface-area due to core–shell morphology has been observed by gas adsorption technique. Treating the granules with hydrofluoric acid, the silica shell has been etched to unwrap the meso-porous carbon core. This demonstrates that the hydrophobic component indeed forms the nano-structured core inside the hydrophilic nano-structured shell. In view of the unique characteristics of these synthesized core–shell nano-structured micro-granules, a potential application of such granules has also been discussed.